The Central Bank of the Russian Federation as a mega-regulator of financial markets - S. Voskovskaya, Anzhela (2020)
The article discloses the concept and types of financial markets. The article analyzes the reasons for creating a mega-regulator of the financial market of Russia and the prospects of its development. The investigation focuses on the functions and powers of the Central Bank of Russia as a mega-regulator of the financial market. As a result of the research, the prospects for the development of the Central Bank of the Russian Federation as a mega-regulator of the financial market are revealed.